Intensive rehabilitation after pelvic and hip fractures: a comparative retrospective study - Katz, Dori; Geftler, Alex; Abu-Ajaj, Ahmed; Makulin, Evgeni; Star, Eva; Zikrin, Evgeniya; Shacham, David; Velikiy, Natalia; Freud, Tamar; Press, Yan (Frontiers in Medicine, 2024)
Purpose Pelvic fracture (PF) is common, especially among older patients, and its prevalence increases over time. In contrast to hip fracture (HF), the literature on rehabilitation after PF is scant, mandating a study of the outcomes of rehabilitation in patients with PF. The present study compared patients who underwent intensive rehabilitation following HF or PF. Methods A retrospective study of patients 65 years of age and older who underwent intensive rehabilitation in the Geriatrics Department. Data were collected on patients with PF, while data on patients with HF were taken from an earlier study. All patients in both groups suffered from low-energy trauma. Rehabilitation outcomes were measured using the Montebello Rehabilitation Factor Score-revised (MRSF-R). Results 144 PF patients were compared with 138 HF patients. The mean age of the patients in the HF group was 82.5 ± 7.1 compared to 81.5 ± 6.9 in the PF group (p = 0.230). Females comprised 77.5% of the patients in the HF group and 90.3% in the PF group (p = 0.04). All patients in the HF group underwent surgical repair of their fracture, while all patients in the PF group had non-surgical treatment. More patients in the HF sample had a nursing caregiver prior to the fracture (92.0% vs. 60.4%, p < 0.001), had a higher Charlson Co-morbidity Index total score (2.1 ± 1.9 vs. 1.6 ± 1.7, p = 0.13), developed more delirium (21.7% vs. 8.3%, p = 0.16), more infections (29.0% vs. 11.1%, p < 0.002), and more cardiovascular complications (23.9% vs. 5.6%, p < 0.001) during hospitalization. They had longer hospital stays (20.9 ± 7.5 vs. 18.2 ± 7.7 days, p = 0.0007), and had a higher mortality rate (13.8% vs. 6.3%, p = 0.037) over the first year following the fracture than the PF group. A similar rate of patients in both groups (64.5% vs. 60.4%, p = 0.483) had successful intensive rehabilitation. In the PF group only cognitive state was an independent predictor of successful rehabilitation, with each additional point in the Mini Mental State Examination (MMSE) increasing the patient’s chance of reaching an MRFS-R score ≥ 50 by 20.5%. Conclusion Despite slightly different characteristics in the two groups, the results of intensive rehabilitation were similar. Cognitive state was the only independent factor that affected achievement of a better rehabilitation outcome. With the increasing rate of PF, more studies should focus on rehabilitation in this patient population.